CANONICAL QUANTIZATION OF DISSIPATIVE SYSTEMS - Jarab’ah, Ola A.; Nawafleh, Khaled I.; Ghassib, Humam B. (European Scientific Journal, ESJ, 2013)
The canonical method is invoked to quantize dissipative systems using the WKB approximation. The wave function is constructed such that its phase factor is simply Hamilton’s principal function. The energy eigenvalue is found to be in exact agreement with the classical case. To demonstrate our approach, the three examples considered in our previous work (ESJ 9(30), 70-81, 2013) are quantized in detail: the damped harmonic oscillator, a system with a variable mass, and a charged particle in a magnetic field.